STRATEGI SEKOLAH DALAM MENCETAK GENERASI QUR’ANI - Ari Retno Marlangen; Anita Puji Astutik; Eni Fariyatul Fahyuni (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The Qur'an is a revelation from Allah SWT which was revealed to the prophet Muhammad SAW through the angel Gabriel which must be practiced. Practicing the Al-Qur'an is not only through reading and studying but can be done by memorizing or understanding the meaning of each verse in the Qur'an. Currently, the interest in memorizing is increasing which makes competition in the world of education more intense in terms of improving the quality of good memorization so that SMA Muhammadiyah 1 Taman School institutions give birth to ideas by making the tahfidz program an arena where students can focus on improving memorization while at the same time molding students to become generations of the Koran. The generation of Qur'ani is an aspiration and hope of every Muslim. The Qur'anic Generation are Muslims who always make the Qur'an a way of life by reading, memorizing, and even practicing and believing in its existence. To make ourselves a Qur'anic generation, we must focus on three things, namely: heart, mind, and body. This study aims to determine the strategy of SMA Muhammadiyah 1 Taman in printing the generation of the Koran. This study used a qualitative method with a field research approach. Data collection techniques using observation, interviews, and documentation. The results obtained from this study are SMA Muhammadiyah 1 Taman embodying a strategy in printing Qur'an generations in the form of the tahfidz program where the program includes intra-curricular activities that use 2 methods, namely muraja'ah and talaqqi